Investigation of physicochemical characterization, thermal inactivation kinetics of enzymes, and shelf-life study of pandan coconut water with honey addition - Z.Q. Sum; A.S. Yusri; N.M. Sarbon (Food Chemistry Advances, 2025)
The physicochemical, thermal inactivation, enzyme kinetics, and shelf-life study of pandan coconut water with various honey incorporations (0–15 %) and with and without heat treatment (80 °C and 25 °C) are examined in this study. The findings showed that pandan coconut water with Kelulut and Tualang honey increased in sugar, minerals, and phenolic content as the honey concentration (0–15 %) increased. The turbidity of the pandan coconut water increased, and its pH significantly decreased (p < 0.05) with the addition of Kelulut and Tualang honey. Polyphenol oxidase and peroxidase in pandan coconut water undergo thermal inactivation kinetics after being heated to 80 °C due to the increasing honey concentration within the formulation. Compared to Tualang honey, pandan coconut water containing Kelulut honey exhibited reduced total plate, yeast, and mold levels. Therefore, this study found that incorporating Kelulut honey into pandan coconut water enhanced its composition and physicochemical properties. It also contributed to the effective thermal inactivation of enzymes, resulting in a longer shelf-life.